RNA Bioinformatics - Picardi, Ernesto; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
This volume provides an overview of RNA bioinformatics methodologies, including basic strategies to predict secondary and tertiary structures, and novel algorithms based on massive RNA sequencing. Interest in RNA bioinformatics has rapidly increased thanks to the recent high-throughput sequencing technologies allowing scientists to investigate complete transcriptomes at single nucleotide resolution. Adopting advanced computational technics, scientists are now able to conduct more in-depth studies and present them to you in this book. Written in the highly successful Methods of Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and equipment, step-by-step, readily reproducible bioinformatics protocols, and key tips to avoid known pitfalls. Authoritative and practical, RNA Bioinformatics seeks to aid scientists in the further study of bioinformatics and computational biology of RNA.
Free Energy Minimization to Predict RNA Secondary Structures and Computational RNA Design -- RNA Secondary Structure Prediction from Multi-aligned Sequences -- A Simple Protocol for the Inference of RNA Global Pairwise Alignments -- De Novo Secondary Structure Motif Discovery Using RNAProfile -- Drawing and Editing the Secondary Structure(s) of RNA -- Modeling and Predicting RNA Three-dimensional Structures -- Fast Prediction of RNA-RNA Interaction Using Heuristic Algorithm -- Quality Control of RNA-Seq Experiments -- Accurate Mapping of RNA-seq Data -- Quantifying Entire Transcriptomes by Aligned RNA-Seq Data -- Transcriptome Assembly and Alternative Splicing Analysis -- Detection of Post-transcriptional RNA Editing Events -- Prediction of miRNA Targets -- Using Deep Sequencing Data for Identification of Editing Sites in Mature miRNAs -- NGS-Trex: An Automatic Analysis Workflow for RNA-Seq Data -- e-DNA Meta-barcoding: From NGS Raw Data to Taxonomic Profiling -- Deciphering Metatranscriptomic Data -- RIP-Seq Data Analysis to Determine RNA-protein Associations -- The ViennaRNA Web Services -- Exploring the RNA Editing Potential of RNA-Seq Data by ExpEdit -- A Guideline for the Annotation of UTR Regulatory Elements in the UTRsite Collection -- Rfam: Annotating Families of Non-coding RNA Sequences -- ASPicDB: A Database Web Tool for Alternative Splicing Analysis -- Analysis of Alternative Splicing Events in Custom Gene Datasets by AStalavista -- Computational Design of Artificial RNA Molecules For Gene Regulation.
Keywords: Bioinformatics; Proteins .; Bioinformatics; Protein Structure